Kondisi Sanitasi Rumah Penderita TB Paru - Lestari, Dwanti; Masra, Ferizal (MIDWIFERY JOURNAL, 2023)
Background: Tuberculosis or often called TB is an infectious disease caused by Mycobacterium tuberculosis, which can be caused by Mycobacterium tuberculosis. attacks the lungs and other organs. The source of transmission of this disease is TB patients, especially patients who contain TB germs in their sputum. When the patient coughs or sneezes, the patient spreads germs into the air in the form of phlegm droplets.Purpose: Get an overview of the condition of the house in pulmonary TB patients in the working area of the Puskesmas Rajabasa Inpatient, South LampungMethods: This research is descriptive study. It was carried out in March 2022. The population as well as the sample for this study were all the houses with pulmonary TB patients, which were registered at the Puskesmas Rajabasa Inpatient from January to December 2021 as many as 38 patients.Results: The results of the research that have been carried out are 38 respondents. regarding the discussion of the condition of the house in patients with pulmonary TB who do not meet the requirements, including 55.3%, Humidity 78.9%, Lighting 47.4%, Floor 15.8%, Walls 23.7%, and Density of occupants of the house 68.4%Conclusion: The condition of the houses of pulmonary TB sufferers in the working area of Puskesmas Rajabasa is still a risk factor for pulmonary TB disease for residentssuggestion: Puskesmas must continue to socialize and educate the public about the dangers of pulmonary TB, as well as outreach about efforts that must be made by the community so that this disease can be prevented Keywords: Tuberculosis, Healthy House, Ventilation, Humidity ABSTRAK Latar Belakang: Tuberculosis atau sering disebut TBC adalah penyakit menular yang disebabkan oleh Mycobacterium tuberculosis, yang dapat menyerang paru dan organ lainnya. Sumber penularan penyakit ini adalah pasien TBC terutama pasien yang mengandung kuman TBC dalam dahaknya. Pada waktu batuk atau bersin, pasien menyebarkan kuman ke udara dalam bentuk percikan dahak.Tujuan: Mendapatkan gambaran kondisi rumah pada penderita TB Paru di wilayah kerja Puskesmas Rawat Inap Rajabasa Lampung SelatanMetode: Penelitian ini bersifat deskriptif yaitu untuk mendapatkan gambaran keadaan rumah penderita TB Paru di wilayah kerja Puskesmas Rawat Inap Rajabasa Lampung Selatan. Dilaksanakan pada bulan Maret 2022. Populasi sekaligus sebagai sampel penelitian ini adalah seluruh rumah penderita TB paru, yang teregistrasi pada Puskesmas Rawat Inap Rajabasa dalam kurun waktu bulan januari sampai bulan desember 2021 sebanyak 38 penderita.Hasil: Kondisi yang tidak memenuh syarat rumah penderita TB Paru diantaranya adalah ventilasi 55,3%, kelembaban 78,9%, pencahayaan 47,4%, lantai 15,8%, dinding 23,7%, dan kepadatan hunian 68,4%.Kesimpulan: Kondisi rumah penderita TB Paru di wilayah kerja Puskesmas Rajabasa masih merupakan faktor resiko terjadi penyakit TB Paru bagi penghuninyaSaran: Pihak Puskesmas harus terus melakukan sosialisasi dan edukasi kepada masyarakat tentang bahayanya penyakit TB Paru, dan sosialisasi tentang upaya-upaya yang harus dilakukan masyarakat agar penyakit ini dapat dicegah Kata kunci: TB Paru, Rumah Sehat, ventilasi, kelembaban